Relationship between Smoking and Outcomes after Cubital Tunnel Release - Crosby, Nicholas E.; Nosrati, Naveed N.; Merrell, Greg; Hasting, Hill, II (Journal of Hand and Microsurgery, 2018)
Purpose Several studies have drawn a connection between cigarette smoking and cubital tunnel syndrome. One comparison article demonstrated worse outcomes in smokers treated with transmuscular transposition of the ulnar nerve. However, very little is known about the effect that smoking might have on patients who undergo ulnar nerve decompression at the elbow. The purpose of this study is to evaluate the effect of smoking preoperatively on outcomes in patients treated with ulnar nerve decompression.Materials and Methods This study used a survey developed from the comparison article with additional questions based on outcome measures from supportive literature. Postoperative improvement was probed, including sensation, strength, and pain scores. A thorough smoking history was obtained. The study spanned a 10-year period.Results A total of 1,366 surveys were mailed to former patients, and 247 surveys with adequate information were returned. No significant difference was seen in demographics or comorbidities. Patients who smoked preoperatively were found to more likely relate symptoms of pain. Postoperatively, nonsmoking patients generally reported more favorable improvement, though these findings were not statistically significant.Conclusion This study finds no statistically significant effect of smoking on outcomes after ulnar nerve decompression. Finally, among smokers, there were no differences in outcomes between simple decompression and transposition.
Keywords: smoking; ulnar nerve; cubital tunnel